Optimized Method for Pseudomonas aeruginosa Integrative Filamentous Bacteriophage Propagation - Gavric, Damir; Knezevic, Petar (Frontiers in Microbiology, 2022)
Filamentous bacteriophages frequently infect Pseudomonas aeruginosa and alter its phenotypic traits, including virulence factors. The first step in examination of these phages is to obtain suspensions with high virus titer, but as there are no methods for integrative filamentous phage multiplication, the aim was to design, describe and compare two methods for this purpose. As models, three strains of Pseudomonas aeruginosa, containing (pro)phages Pf4, Pf5 and PfLES were used (PAO1, UCBPP-PA14, and LESB58, respectively). The method 1 comprised propagation of phages in 6 liters of bacterial culture for 48h, and the method 2 applied 600 mL culture and incubation for 6 days, with centrifugation and addition of new medium and inoculum at two-day intervals. In the method 1, phages were propagated by culture agitation, followed by centrifugation and filtration (0.45 and 0.22 µm), while in the method 2 cultures were agitated and centrifuged several times to remove bacteria, without filtration. Regardless of the propagation method, supernatants were subjected to concentration by PEG8000 and CsCl equilibrium density gradient centrifugation, and phage bands were removed after ultracentrifugation and dialyzed. In the obtained suspensions, phage titer was determined and concentration of isolated ssDNA from virions was measured. When propagation method 2 was compared to method 1, the phage bands in CsCl were much thicker, phage number was 3.5 to 7.4 logs greater and concentration of ssDNA was 7.6 up to 22.4 times higher. When phage count was monitored from day 2 to day 6, virion numbers increased for 1.8-5.6 logs, depending on phage. We also observed that filamentous phage plaques faded after 8 h of incubation when double layer agar spot method was applied, while the plaques were visible for 24 hours on single layer agar. Finally, for the first time we confirmed existence of replicative form and virions of PfLES (pro)phage , as well as its ability to produce plaques. Similarly, for the first time we confirmed plaque production of Pf5 (pro)phage present in P. aeruginosa strain UCBPP-PA14. The described method 2 has many advantages, can be further improved and adopted for filamentous phages of other hosts.